LUTEMBACHER’S SYNDROME - A CASE REPORT - SM, Biradar; Malgar, Nilesh (International Journal of Clinical and Biomedical Research, 2017)
Lutembacher’s syndrome is a rare heart disease comprises ASD secundum with mitral stenosis. Here we will discuss a case of 28 years old man, non-diabetic, non-hypertensive, admitted in BLDE Hospital on 10-04-2017 with complaints of respiratory distress and chest pain for 10 days. On detailed examination and investigation, he was found to be having Lutembacher’s syndrome. Key words: Atrial septal defect; Lutembacher’s syndrome; Mitral stenosis.